Problem-Based Learning in Pharmaceutical Education: A Systematic Review and Meta-Analysis - Tais F. Galvao; Marcus T. Silva; Celiane S. Neiva; Laura M. Ribeiro; Mauricio G. Pereira (The Scientific World Journal)
Objective. To assess the effects of problem-based learning (PBL) on the learning achievements of pharmacy students. Methods. We searched for controlled studies that compared PBL to traditional learning in pharmacy courses (graduate and undergraduate) in the major literature databases up to January 2014. Two independent researchers selected the studies, extracted the data, and assessed the quality of the studies. Meta-analyses of the outcomes were performed using a random effects model. Results. From 1,988 retrieved records, five were included in present review. The studies assessed students’ impressions about the PBL method and compared student grades on the midterm and final examinations. PBL students performed better on midterm examinations (odds ratio [OR]=1.46; confidence interval [IC] 95%: 1.16, 1.89) and final examinations (OR=1.60; IC 95%: 1.06, 2.43) compared with students in the traditional learning groups. No difference was found between the groups in the subjective evaluations. Conclusion. pharmacy students’ knowledge was improved by the PBL method. Pharmaceutical education courses should consider implementing PBL.